NEPA implementation and trust: linking stakeholder trust to substantive effectiveness in U.S. Forest Service fuels reduction projects - Hall, Hailey R., author; Scott, Ryan, advisor; Gottlieb, Madeline, committee member; Schultz, Courtney, committee member (Colorado State University. Libraries, 2022)
Trust matters; but, rather than take it as a given, this study presents an empirical snapshot of how trust matters, what types of trust matter, and how those trust types interact within and on National Environmental Policy Act (NEPA) substantive effectiveness. I define substantive effectiveness as the degree to which the policy meets its established aims of considering environmental effects and including the public in the process. Using documents and public comments from two U.S. Forest Service (USFS) Fuels Reduction projects in the Boulder Ranger District in Colorado, I assessed stakeholder trust judgements by coding trust types and frequencies. I then used process tracing to examine how stakeholder trust types interact with one another and relate to substantive effectiveness. I found that interpersonal trust, interpersonal distrust, and institutional distrust play prominent but varied roles within the NEPA process. First, interpersonal trust mediates the effect of institutional distrust on the substantive effectiveness of the NEPA process. Second, higher levels of institutional and interpersonal distrust result in more substantive changes in the NEPA environmental assessment process. Through improved understanding of the roles and functions of stakeholder trust types on the NEPA process, we add nuanced understanding to established expectations of how trust and distrust operate within natural resource planning and management.